2000
DOI: 10.1590/s0004-282x2000000100027
|View full text |Cite
|
Sign up to set email alerts
|

Orbital myositis and rheumatoid arthritis: case report

Abstract: -Orbital myositis implies orbital inflammation confined to one or more of the extraocular muscles. The acute form responds well to high doses of oral corticosteroids tapered gradually, but it may recur or become chronic. We describe a 38 years old female who has been suffering from rheumatoid arthritis for six years. She developed diplopia as a result of a paralysis of the right and left rectus medialis muscle. MRI showed inflammatory process and thickness of the referred muscles. The patient had a total recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
(29 reference statements)
0
16
0
1
Order By: Relevance
“…Both cases responded well to a temporary increased dose of oral prednisone [126,127]. In another case of RA-associated OID, disease had been well controlled on regular adalimumab when the patient developed orbital involvement.…”
Section: Rheumatoid Arthritismentioning
confidence: 96%
See 1 more Smart Citation
“…Both cases responded well to a temporary increased dose of oral prednisone [126,127]. In another case of RA-associated OID, disease had been well controlled on regular adalimumab when the patient developed orbital involvement.…”
Section: Rheumatoid Arthritismentioning
confidence: 96%
“…Although exceedingly rare, orbital manifestations, including myositis [126,127] and diffuse orbital inflammatory disease (OID) [128], have been reported in patients with RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Other patients developed a myositis with enlargement of the muscles on CT. 83,84,86 Reported cases of orbital inflammation in RA mostly involve patients with limited extraocular movements secondary to a myositis. Nabili et al 92 and Panfilio et al 93 reported cases of extraocular muscle enlargement in patients with a prior history of RA. Orbital biopsy was not performed in either case, therefore it is difficult to determine the exact etiology of the myositis.…”
Section: Systemic Lupus Erythematosis and Rheumatoid Arthritismentioning
confidence: 99%
“…Patients in the literature have been successfully treated with oral or IV glucocorticoids. [81][82][83][84][85][86][87][88][89][90][91][92][93] Most patients had complete resolution of symptoms after initiating therapy, although there were four cases in which the patients had a recurrence of disease and needed an increase in dosage. [89][90][91] Treatment with steroids was always in addition to their ongoing treatment for SLE or RA.…”
Section: Systemic Lupus Erythematosis and Rheumatoid Arthritismentioning
confidence: 99%
“…A common feature of many autoimmune diseases is the deposition of autoantibody in tissues at various sites around the body, leading to the fixation and activation of complement, and resulting in generation of the inflammatory response 7 . Reports describe development of localized IOI in patients with RA 8,9 , the first of which describes successful treatment of a 38-year-old woman with a 6-year history of seropositive RA, with high-dose methylprednisolone 9 . However, despite use of IV methylprednisolone and MTX in our case, symptom resolution is attributed to RTX alone.…”
Section: To the Editormentioning
confidence: 99%